PENGARUH MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR LURAH ONA’TALI, KECAMATAN ROTE TENGAH, KABUPATEN ROTE NDAO - Marselinda Hege (P3M Politeknik Negeri Ambon, 2023)
The purpose of this writing is to find out how much positive and significant influence motivation has on the performance of employees at the Onatali Village Head Office, Rote Tengah District, Rote Ndao Regency. The data collection techniques used in this writing are observation techniques, questionnaires and interviews. The raw data obtained was processed using the SPSS 25 computer application using simple linear regression analysis and the t test significance test. The writing results show that there is a positive and significant influence between motivation on employee performance at the Onatali Village Head Office, Rote Tengah District, Rote Ndao Regency with the regression equation Y = 7.089+0.634X. The results of the significance test using the t test show that the tcount of 3.241 is greater than the table value of 1.943.